Animated potentiality: Temporality and the limits of narrativity in anime - González Torrents, Alba (2015)
The purpose of this paper is to explore, through several concepts extracted from the philosophies of Henri Bergson, Gilbert Simondon and Gilles Deleuze, the relationship between narrative and extra-narrative elements in anime such as Revolutionary Girl Utena, Serial Experiments Lain and Puella Magi Madoka Magica. In these works we are presented not only with complex narratives, but also elements that seem to escape narrative logic (for example, the unexplained appearance of images, colors and sounds). Both the constantly "floating" extra-narrative aspects and specific points of rupture in the narrative have to be duly accounted for. I will relate the analysis of these anime to two forms of temporality, i.e. the product-time and process-time (closer to Bergson´s durée). The former shall be applied to the structure of the narrative parts, and the later to the role of the extra-narrative elements. I will specifically focus on the difference between the individual / environment pair, which taken as a whole constitutes the ending point of the Simondonian ontogenesis, and that which exceeds individuation: "apeiron", the undetermined understood as a place of potentiality. Ultimately the paper aims at demonstrating how anime functions as what I call a "thinking device"